Active 650-km Long Fault System and Xolapa Sliver in Southern Mexico - Kazachkina, Ekaterina; Kostoglodov, Vladimir; Cotte, Nathalie; Walpersdorf, Andrea; Ramirez-Herrera, Maria Teresa; Gaidzik, Krzysztof; Husker, Allen; Santiago, Jose Antonio (Frontiers in Earth Science, 2020)
New estimates of long-term velocities of permanent GPS stations in Southern Mexico reveal that the geologically discernible ~650 km long shear zone, which strikes parallel to the Middle America trench, is active. This left-lateral strike-slip La Venta-Chacalapa (LVC) fault system is apparently associated with a motion of the Xolapa terrain, and at the present time is the northern boundary of a ~110 – 160 km wide forearc sliver with a sinistral motion of 3 – 6 mm/yr with respect to the North America plate. This sliver is the major tectonic feature in the Guerrero and Oaxaca regions, which accommodates most of the oblique component of the convergence between the Cocos and North America plates. Previous studies based purely on the moment tensor coseismic slips exceedingly overestimated the sliver inland extent and allocated its northern margin on or to the north of the Trans-Mexican Volcanic Belt. While the LVC fault system probably slips slowly over geologic scale time, and there is not any historic evidence of large earthquakes on the fault so far, its seismic potential could be very high assuming a feasible order of ~103 years recurrence cycle. A detailed analysis of long-term position time series of permanent GPS stations in the Guerrero and Oaxaca states, Southern Mexico discards previous models and provides clear evidence of an active LVC fault zone bounding the Xolapa forearc sliver. The southeastward motion of this sliver may have persisted for the last ~8-10 Myr and played an important role in the tectonic evolution of the region.